Empowering Community Leaders to Prevent and Control Lung Tuberculosis in Manado City: A Quasi-experimental Study - Dionysius Sumenge (Universitas Airlangga, 2022)
Background: Lung tuberculosis (TB) is a global public health problem as it continues to be a major cause of morbidity and mortality worldwide. According to WHO, as many as 44% of lung TB cases were in the Southeast Asian region. A previous study showed the importance of the support of community leaders and health cadres in increasing knowledge and improving public attitudes towards the prevention and control of lung TB. Objective: This study aims to determine the effectiveness of health education in empowering community leaders to prevent and control lung TB in four Public Health Centres in Manado City. Methods: A quasi-experiment with pre and post-design was used to answer the research hypothesis. With cluster sampling, four Public Health Centres in Manado City were selected based on their geographical location. Community leaders were selected according to the inclusion criteria using a convenience sampling technique. One hundred community leaders from the four Public Health Centres agreed to participate. Health education used the newly developed printed and e-posters accessed through YouTube. The health education was conducted once for each group according to the respondents’ convenient time. Questionnaires collected knowledge and attitudes data before and after the educational program from July to August 2021. Results: Sixty percent of respondents were women, and most of their education level was Senior High School. Wilcoxon signed-rank test results for the knowledge variable and paired t-test for the attitude variable showed a significant difference (P-value < 0.05). Results indicated an increase in knowledge and a positive change in attitudes of the community leaders after the health education. Conclusion: Findings from this study showed that the educational program was highly effective in empowering community leaders to prevent and control lung TB in four Public Health Centers in Manado.